Factors Related to Depression Level among Malaysian Students Batch 2015-2018 in Universitas Sumatera Utara - Jesvinder Amaiappan; Putri Chairani Eyanoer (Journal of Epidemiology and Public Health, 2020)
Background: Depression is the most common psychological disorder encountered and is a disorder that is mainly characterized by sad and depressed emotional conditions and is associa